Caring Behaviors and Therapeutic Communication Among Third-Year Nursing Students During Service at Santa Elisabeth College of Health Sciences Medan - Mestiana Br. Karo; Cyndi Monika Hutasoit (JURNAL RISET RUMPUN ILMU KESEHATAN, 2024)
Caring behavior encompasses compassion, empathy, responsibility, sensitivity, and supportive actions that shape quality nursing care. Therapeutic communication, as a structured and goal-directed interaction, is essential for facilitating patient recovery and meeting client needs. This study aimed to describe the caring behavior and therapeutic communication competencies of third-year nursing students during clinical practice. A descriptive method was applied used cross sectional design, involving all 97 students selected through a total sampling method. Data were collected using validated questionnaires on caring behavior and therapeutic communication, and analyzed bivariate using frequency and percentage distributions. Results showed that 50 students (51.5%) demonstrated very good caring behavior, whereas only 9 students (9.3%) achieved sufficient levels of therapeutic communication. These findings underscore the importance of strengthening training strategies to enhance students’ caring competencies and therapeutic communication skills, thereby improving the effectiveness and quality of nursing practice. It is hoped that strengthening these skills will help nursing students overcome challenges in clinical practice and contribute to more effective patient recovery.